Analisis Laporan Keuangan untuk Menilai Kesehatan Bank Berdasarkan Rasio Profitabilitas dan Rasio Likuiditas pada Bank Maybank Tahun 2019-2023 - Zahira, Silvia Nazma; Aisyah, Esy Nur (Maliki Interdisciplinary Journal, 2025)
This study analyzes the financial statements of Bank Maybank from 2019 to 2023 to assess its financial health through profitability and liquidity ratios. The research reveals that despite a decline in performance in 2020 due to the pandemic’s impact, the bank exhibited a positive recovery trend in the subsequent years. Ratios such as Return on Assets (ROA) and Return on Equity (ROE) are utilized to evaluate the bank’s ability to generate profits from its assets and equity. Additionally, the analysis of liquidity ratios like Loan to Deposit Ratio (LDR) indicates that the bank has managed to maintain a balance between liquidity and productivity. The findings of this research are expected to contribute valuable insights for investors, management, and regulators in making informed decisions related to banking in Indonesia.